Quality culture and its role in developing strategies for teaching art education in accordance with the educational reform movement (Journal of the College of Basic Education, 2024)
The aim of the current research is to reveal the standards of quality culture and identify its role in developing strategies for teaching art education in accordance with the educational reform movement. The researcher followed the descriptive and analytical approach that is compatible with her research procedures. For the purpose of achieving the research objectives, the researcher built two questionnaires. The first was to determine the relationship between the standards of quality culture. And between the strategies for teaching art education, and the second to determine the extent of compatibility of strategies for teaching art education with the principles of the educational reform movement in light of the standards of quality culture, and the five-point Lickert scale was adopted, which includes five numerical grades (5, 4, 3, 2, 1). The research sample consisted of teachers. In the departments of art education in Iraqi universities, the questionnaires were characterized by validity and reliability, and the existence of a correlation between the research variables was tested, and the existence of a significant effect was verified or not, and the nature of the relationship between the variables was known. Linear regression was also used to determine the presence of a moral effect or not between the variables at the level of significance. (0.05). As for verifying the nature of the relationship between the variables, the Pearson correlation coefficient was used according to the following standards: from (- 0.5 to 0.1) is considered a weak correlation, and from (0.51 - 0.70 is considered a moderate correlation, and (0.71 - 0.9) is considered a strong correlation. The significance of the relationship was accepted at a significance level of (0.05) and above. The results showed the existence of a strong and statistically significant correlation between the criteria. Quality culture and the development of strategies for teaching art education historically in accordance with the educational reform movement. It emerged from the results of the correlation that the most responsive strategies to development according to the standards of quality culture are (brainstorming, diaspora coalition, task analysis, discovery, role-playing, cooperative learning, concept map). The correlation was very strong and statistically significant in all its criteria.